2019
DOI: 10.15520/jcmro.v2i10.214
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Dosimetric analysis of Bone marrow sparing vs non bone marrow sparing Image Guided Volumetric Modulated Arc Therapy in intact Carcinoma Cervix patients

Abstract: Aim: Aim of this study was to compare dosimetric parameters of bone marrow (BM) and non bone marrow sparing with state of the art technique image guided volumetric modulated arc therapy in the treatment of Carcinoma Cervix. Methods and Materials: The retrospective Dosimetric study was conducted on 10 consecutive patients of biopsy-proven invasive cervical cancer attending the outpatient department of Geetanjali cancer centre. For treatment planning, patients were scanned on a GE Optima-520, 16 slice fan-beam C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…This is inconsistent with literature that has reported bone marrow doses were reduced at all levels, shown in 4. 13,14,16,17 Despite the lack of significance of the V30-40Gy in our study in comparison with the original VMAT group, ABM objective compliance was improved from 50% to 100% for the V30Gy, and 50% to 83.3% for the V40Gy. Furthermore, our actual dose reduction at the V30Gy is comparable to that reported by Liang et al, which was significant at all dose levels.…”
Section: Abm Dosescontrasting
confidence: 72%
See 4 more Smart Citations
“…This is inconsistent with literature that has reported bone marrow doses were reduced at all levels, shown in 4. 13,14,16,17 Despite the lack of significance of the V30-40Gy in our study in comparison with the original VMAT group, ABM objective compliance was improved from 50% to 100% for the V30Gy, and 50% to 83.3% for the V40Gy. Furthermore, our actual dose reduction at the V30Gy is comparable to that reported by Liang et al, which was significant at all dose levels.…”
Section: Abm Dosescontrasting
confidence: 72%
“…This overestimates the bone marrow contours, leading to over-optimisation of these contours and constraining the optimisation process. 13,17 Prospective trials in this area are few, with Mell et al conducting the only trial investigating FDG-PET-defined ABM specifically in cervical cancer (n = 83) reporting reductions in the rate of HT. 14 Despite the differences in ABM delineation, all studies demonstrated, dosimetrically, that dose to the ABM can be reduced without compromise of target coverage or organs at risk (OAR) dose.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations